2021
DOI: 10.3390/ijms22094377
|View full text |Cite
|
Sign up to set email alerts
|

Role of Short Chain Fatty Acids and Apolipoproteins in the Regulation of Eosinophilia-Associated Diseases

Abstract: Eosinophils are key components of our host defense and potent effectors in allergic and inflammatory diseases. Once recruited to the inflammatory site, eosinophils release their cytotoxic granule proteins as well as cytokines and lipid mediators, contributing to parasite clearance but also to exacerbation of inflammation and tissue damage. However, eosinophils have recently been shown to play an important homeostatic role in different tissues under steady state. Despite the tremendous progress in the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 258 publications
2
8
0
Order By: Relevance
“…In coronary artery disease patients, an inverse association of absolute eosinophil count and HDL cholesterol and a positive association with the prevalence of coronary artery disease was reported [ 250 ]. Both HDL and HDL apolipoproteins were recently shown to effectively inhibit eosinophil chemotaxis [ 29 ] and to attenuate eosinophil activation [ 251 ]. In a study involving atopic dermatitis patients, patients’-derived HDL showed an impaired ability to inhibit agonist-induced eosinophil shape change and migration compared to HDL isolated from healthy controls [ 34 ].…”
Section: Immunomodulatory Functions Of Hdlmentioning
confidence: 99%
“…In coronary artery disease patients, an inverse association of absolute eosinophil count and HDL cholesterol and a positive association with the prevalence of coronary artery disease was reported [ 250 ]. Both HDL and HDL apolipoproteins were recently shown to effectively inhibit eosinophil chemotaxis [ 29 ] and to attenuate eosinophil activation [ 251 ]. In a study involving atopic dermatitis patients, patients’-derived HDL showed an impaired ability to inhibit agonist-induced eosinophil shape change and migration compared to HDL isolated from healthy controls [ 34 ].…”
Section: Immunomodulatory Functions Of Hdlmentioning
confidence: 99%
“…The entry of SCFAs into the systemic bloodstream may be due both to passive diffusion and to the participation of special transporters, such as monocarboxylate transporter 1 (MCT1) and sodium-bound monocarboxylate transporter 1 (SMCT1) [ 198 ]. MCT1 has also been detected in cells of the immune system, including lymphocytes, monocytes, and neutrophils [ 210 , 211 ].…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…SCFAs are thought to realize their action through inhibition of histone deacetylase (HDAC) and through interaction with the G-protein-related receptors GPR43 and GPR41, also known as free fatty acid receptor (FFA)2 and FFA3, respectively [ 211 , 212 , 213 , 214 ]. In addition, the receptors for SCFAs are GPR109a (also known as HCA2) and olfactory receptor 78 (Olfr78) [ 215 , 216 , 217 ].…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations